Oxford world watch Geography 1 skills book grade 6 - Moorcroft, Christine (Karachi : Oxford university press, 2023)
The "Oxford World Watch Geography 1 Skills Book" for Grade 6 helps students develop basic geographical skills, such as reading maps and understanding global patterns. It covers topics like climate, ecosystems, landforms, and population, using engaging activities to build a strong foundation in geography. The book encourages critical thinking and prepares students for advanced geography studies.
Keywords: Geography : Skillsbook; Oxford : Grade 6